(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The scope and usefulness of smartphone applications (Apps) in ophthalmology are topics that are not well covered in the literature. As a result, eye care professionals are dubious about the advantages of smartphone apps and hesitant to incorporate them into their daily work. This study’s objective was to present an updated overview of all ophthalmology-specific Apps. Methods: For this study, smartphone apps that are just intended for ophthalmic care were quantitatively analyzed. Apps with an eye care theme were looked for in the Apple iPhone and Google Play stores. The study includes all eye-related apps, including those for visual acuity testing, eye education, calculators, eBooks, and low vision aids. Data regarding the apps’ goals, intended end users, validation, app usage, user reviews, and app developers’ credentials were recorded. Results: A total of 140 Apps that are only focused on eye care have been found as of March 2020. 55% of the 140 accessible apps were compatible with iPhones, 45% with Android smartphones, and 4% with both. 30% (42/140) of the Apps were created for visual acuity (VA) testing, 13% (18/140) for eye relaxation exercises, 12% (17/140) for professional development, and the rest Apps were created for color blindness detection, low vision aids, patient education, and assistance. Six (4.2%) of the 140 Apps claim to be validated, according to the developers. This study reveals a variety of smartphone apps that are specific to ophthalmology and offers advice on how to pick the best ones. The study also emphasizes how crucial interdisciplinary cooperation is to the conception, creation, and evaluation of these Apps.